The Effect of Housing Marketing Mix on Purchase Decisions for Type 36 Houses in Jenar, Purworejo Regency - Vicki Dwi Purnomo (PT FORMOSA CENDEKIA GLOBAL, 2022)
As population growth continues to increase, the need for housing is also increasing. Meanwhile, consumers want to get higher quality housing, causing competition in the property industry to become increasingly stringent. To be able to win the competition, the right marketing strategy is needed, one of which is the marketing mix strategy. The purpose of this study was to determine the effect of the marketing mix on home buying decisions either partially or simultaneously and to determine which marketing mix variables have the most dominant influence on home buying decisions, distribution and promotion channels which are the basic variables of the marketing mix as the independent variables and the consumer's home buying decision as the dependent variable. The population studied was all buyers of Housing Type 36 Jenar Purworejo. In this study using a proportional sampling technique based on predetermined criteria, namely the buyer of housing type 36, Jenar Purworejo housing.